Is the level of eye-hand coordination and executive functioning related to performance in para table tennis players? – An explorative study - Irene R. Faber; Johan Pion; Bas Willemse; Willianne Schipper; Maria Nijhuis-Van der Sanden (International Journal of Racket Sports Science, 2019)
The goal of this explorative study was to explore whether eye-hand coordination and executive functions (i.e. cognitive flexibility, attention control and information processing) are related to the performance level in para table tennis players. The data of 11 elite (age 15-54) and 11 non-elite para table tennis players (age 13-49) were analyzed. The results showed that the elite players performed better than the median norm values for cognitive flexibility and attention control while the non-elite players demonstrated slower information processing than the median norm values (p<0.05). The players’ competition rating correlated significantly with the eye-hand coordination, cognitive flexibility and information processing measures (p < 0.05). Players with a competition rating > 1000 points scored ≥ 24 catches per 30 s in the eye hand coordination task, whereas the players with < 1000 rating points score ≤ 18 catches per 30 s. In contrast, there was a clear overlap of scores between the players with > 1000 and < 1000 rating scores in the executive functions tests. The results present a first profile of para table tennis players regarding their eye-hand coordination and executive functions and the relationship of these constructs with the performance level. Long-term international cooperation is recommended to understand the value of the measured constructs to predict future successes.